Mass social media-induced illness presenting with Tourette-like behavior - Fremer, Carolin; Szejko, Natalia; Pisarenko, Anna; Haas, Martina; Laudenbach, Luise; Wegener, Claudia; Müller-Vahl, Kirsten R. (Frontiers in Psychiatry, 2022)
Currently, we are facing a new manifestation of functional neurological disorder presenting with functional Tourette-like behavior (FTB). This study aimed to show characteristics of this phenotype presenting as an outbreak of “mass social media-induced illness” (MSMI) and to explore predisposing factors. Between 5-9/2021, we prospectively investigated 32 patients (mean/median age: 20.1/18 years, range: 11-53 years, n=16 females) with MSMI-FTB using a neuro-psychiatric examination, a comprehensive semi-structured interview and aspects of the Operationalized Psychodynamic Diagnostic System. In contrast to tics, numbers of complex movements and vocalizations were nine times greater than of “simple” symptoms, and of vocalizations one and a half times greater than of movements. In line with our hypothesis of MSMI, symptoms largely overlapped with those presented by German YouTuber Jan Zimmermann justifying his role as “virtual” index case in current outbreak. Typically, symptoms started abruptly at a mean age of 19 years and deteriorated gradually with no differences between males and females. In all patients, we identified timely-related psychological stressors, unconscious intrapsychic conflicts, and/or structural deficits. Nearly all patients (94%) suffered from further psychiatric symptoms including abnormalities in social behavior (81%), obsessive-compulsive behavior (OCB) (47%), Tourette syndrome (TS) (47%), anxiety (41%), and depression (31%), about half (47%) had experienced bullying, and 75% suffered from coexisting somatic diseases. Our data suggest that pre-existing abnormalities in social behavior and psychiatric symptoms (OCB, anxiety, and depression), but also TS in combination with timely-related psychological stressors, unconscious intrapsychic conflicts, and structural deficits predispose to contagion with MSMI-FTB.